English Café Identity Construction: A Critical Discourse Analysis - Muhammad Subhan Fikri (The Study Program of English Education of Palangka Raya University, 2022)
Having a specific identity helps English cafe to be one of popular English courses in Jogjakarta. This research aims to understand the discourses in the social interaction for English cafe identity construction and how each discourse construct its identity as an English learning institution. This research used Critical Discourse Analysis as the approach to answer the question about the identity construction. To collect the data, the researcher used three data collection techniques; interview, observation, and document review. The result of the research is that English cafe uses several media, such as website, social media, banner, poster and flyer, to convey their identity for their future customers. Setting, relationship of the class participants, and interaction modes are parts of the learning process that strengthen the identity construction. Daily talk premium, questionnaire, and management weekly meeting are English cafe’s effort to maintain the construction when there are complaints from its costumers. To conclude, English Cafe has a unique and different concept compared to the other conventional English course. The institution does not only offer a concept, but also constructs its identity in their customers and future customers perception.